(untitled) (European Bison Conservation Newsletter, 2013)
Presented is the history of the region and specially of the Forest District Stuposiany. Already fifty years ago in 1963, first European bison came to forestry Widelki and after short acclimatization were released and created the Eastern part of wisent population. The other reintroduction was done at Wola Michowa. Present population of wisents in Bieszczady is close to 300 individuals. The Forest District Stuposiany is deeply involved in wisent conservation programs and during last time many very good and sad things happened. The tuberculosis caused the neccessity of the whole herd liquidation. On the other hand new education and acclimatization enclosure was built in Muczne. In the future thanks to this enclosure will possible re-creation of the herd in the neigbouring region.